Reformasi Hukum Keluarga Islam di Brunei Darussalam: Studi atas Kodifikasi dan Adaptasi Mazhab Syafi'i dalam Konteks Modern - Septia Nabila; Siska Yani; Nazirah Sukma; Nurul Afifah; Jamilah; Al Aziz; Aulil Amri (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2025)
This article examines the reform of Islamic family law in Brunei Darussalam, emphasizing its statutory codification within a modern state framework while retaining Syafi’i orthodoxy. Using a qualitative library research method, it analyzes regulatory transformations in marriage registration, minimum marriage age, judicially-controlled polygamy, divorce procedures, and obligatory bequest (wasiat wajibah). The findings show that Brunei adopts a strong state-centric legal model—requiring formal registration and court approval for polygamy—making it more centralized than Indonesia but less secular than Malaysia, which permits broader judicial discretion. This model reflects a hybrid approach that preserves Syafi’i legal heritage while institutionalizing bureaucratic control to ensure legal certainty and social order.